Math, asked by jananik933, 1 year ago

Find the value of a and b if 5-2√3÷7-4√3=a-√3b

Answers

Answered by DaIncredible
0

Answer:

a = 11 and b = -6

Step-by-step explanation:

 \frac{5 - 2 \sqrt{3} }{7 - 4 \sqrt{3} }  \\

Rationalizing the denominator we get:

 =  \frac{5 - 2 \sqrt{3} }{7 - 4 \sqrt{3} }  \times  \frac{7 + 4 \sqrt{3} }{7 + 4 \sqrt{3} }  \\  \\  =  \frac{5(7 + 4 \sqrt{3}) - 2 \sqrt{3}(7 + 4 \sqrt{3} )  }{ {(7)}^{2}  -  {(4 \sqrt{3} )}^{2} }  \\  \\  =  \frac{35 + 20 \sqrt{3}  - 14 \sqrt{3}  - 24}{49 - 48}  \\  \\  \bf =  11 + 6 \sqrt{3}  \:

Now, equating L.H.S and R.H.S we get:

11 + 6 \sqrt{3}  = a  - b \sqrt{3}  \\  \\  \bf  a = 11 \:  \:and \:  \:  b =  - 6

Similar questions